EKSTRAK ETANOL BAWANG HITAM (Allium sativum L.) MENURUNKAN KADAR ASAM URAT MENCIT JANTAN MODEL HIPERURISEMIA - Pangala, Gustinara Bakti; Mahendra, Agung Nova; Jawi, I Made; Dewi, Ni Wayan Sucindra (E-Jurnal Medika Udayana, 2022)
Black garlic is garlic that goes through a heating process and has a higher bioactivity of substances. The purpose of this study was to determine the effect of black garlic extract on the reduction of uric acid in male mice with hperuricemia induced by 25 ml / kg of chicken liver juice and 250 mg / kg of potassium oxonate. The mice used were male mice with uric acid levels above 3.3 mg / dL or 6.3-6.8 mg / dL. This research is an experimental study with the method of Pre Test - Post Test Control Group Design. The treatment group was K +: Giving allopurinol suspension 10 mg / kg BW, K-: Giving aquabides to the negative control group of mice, P1: Giving black garlic ethanol extract 4.2 mg / 20gr bb, P2: Giving black garlic ethanol extract 8.4 mg / 20gr bb, P3: Provision of black garlic ethanol extract 12.4 mg / 20gr bb. Measurement of uric acid levels was carried out at D-10 after induction of a high uric acid diet, as well as D-26 after treatment of each group. Data were analyzed by One Way Anova test and post hoc LSD test. The results showed that the ethanol extract of black garlic was able to reduce uric acid levels in the blood of mice with the highest percentage reduction in the P3 group (12.4 mg / 20gr bb) by 31,2%, followed by P2 (8.4 mg / 20gr. bb) of 18,03%. The lowest percentage reduction in uric acid levels was in the P1 group (4.2 mg / 20gr bb) by 10,2%. Black garlic ethanol extract has an effect on reducing total uric acid levels in mice due to its antioxidant content such as flavonoids, polyphenols, 5-hydroxymethylfurfural (5-HMF), leucine, and isoleucine. Key words: Black garlic, hyperuricemia, antioxidants, flavonoids.